An Estimation of Soil Erosion Rate Hot Spots by Integrated USLE and GIS Methods: a Case Study of the Ghiss Dam and Basin in Northeastern Morocco - Taher, Morad; Mourabit, Touafik; Bourjila, Abdelhak; Saadi, Omar; Errahmouni, Ali; El Marzkioui, Fouad; El Mousaoui, Mhamed (Geomatics and Environmental Engineering, 2022)
Soil erosion is a major factor leading to dams´ siltation and reducing their storage capacity. This study mapped the hot spots of soil erosion areas to predict the soil erosion/siltation in the Ghiss basin/dam (northeastern Morocco). In this context, various data has been prepared in the geographical information system for the estimation of soil erosion by integrating the universal soil loss equation (USLE). The result of this study revealed that soil loss rate ranges between 0 and 19 t∙ha^(−1)∙yr^(−1). Therefore, the hot spots in the soil erosion area are to be found upstream, potentially leading to dam siltation over time. To avoid Ghiss dam siltation, we suggest terrace farming and reforestation in the soil erosion area hot spots.